Raman scattering of light in biaxial monocline β-ZnP₂ crystals - Gubanov, V.O.; Kulakovs’kij, V.D.; Poveda, R.A.; Yanchuk, Z.Z. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2001)
In this paper we represent for the first time observed experimental data on non-resonant Raman scattering in a plate of β-ZnP₂. The high-frequency part of RS spectra КР β-ZnP₂ is determined by oscillations of sites in P-atom spirals considered as building units of the β-ZnP₂ lattice. These spirals, as to their oscillatory properties, are very similar to infinite P-atom spirals in α-ZnP₂. Thus, the most intensive RS spectral band 433.0 cm-1 responds to main inphase quasivalence oscillations for all four translations of non-equivalent sites in Р-spirals while bands 448.4; 458.2; 466.3 cm-1 to quasivalence out-of-phase excited oscillations orthogonal to the main ones.